Opinion on the re‐evaluation of mono‐ and diglycerides of fatty acids (E 471) as food additive in foods for infants below 16 weeks of age and follow‐up of their re‐evaluation as food additives for uses in foods for all population groups. (8th November 2021) - ; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gürtler, Rainer; Husøy, Trine; Manco, Melania; Mennes, Wim; et al.
Abstract: Mono‐ and diglycerides of fatty acids (E 471) was re‐evaluated in 2017 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As a follow‐up to this assessment, the Panel on Food Additives and Flavouring was requested to assess mono‐ and diglycerides of fatty acids (E 471) for its use as food additive in food for infants below 16 weeks of age belonging to food categories 13.1.1 (Infant formulae) and 13.1.5.1 (Dietary foods for infants for special medical purposes and special formulae for infants). In addition, the FAF Panel was requested to address the issues already identified during the re‐evaluation of the food additive in 2017 when used in food for the general population. The Panel considered that there is no indication of adverse effects from the available animal studies at the highest dose tested and from the post marketing data. A comparison was made between the daily exposure to the sum of mono‐ and di‐acylglycerols from breast milk and that resulting from the use of E 471 in the infant formula. The Panel noted that the resulting exposures are in the same order of magnitude. Overall, the Panel concluded that there is no reason for a safety concern when E 471 used as food additive in FC 13.1.1 and 13.1.5.1 and according to the Annex III to Regulation (EC) No 1333/2008. The risk assessment for toxic elements and impurities clearly indicated the need to lower the current maximum limits for arsenic, lead, cadmium and mercury and to include limits for glycidyl esters, 3‐monochloropropane diol and erucic acid in the EU specifications of E 471.